Comparative Study of Fly Ash/Sugarcane Fiber Reinforced Polymer Composites Properties - Md Rezaur, Rahman; Elammaran, Jayamani; Deshan, Anselam Benhur; Muhammad Khusairy, Bin Bakri; Akshay, Kakar; Afrasyab, Khan (NC State University, 2020)
This paper discusses mechanical, morphological, infrared spectral, and thermal properties of fly ash/sugarcane fiber reinforced epoxy polymer composites. Samples were prepared with and without the addition of 2 wt% of fly ash. Sugarcane fiber additions were varied from 0 wt% to 10 wt% (with an increment of 2 wt% for each sample), while the epoxy was used as a binder. A comparative study of these properties was completed on samples with and without the addition of fly ash in the composites. Based on the results obtained, the addition of 2 wt% of fly ash improved the tensile strength and hardness properties but reduced the flexural strength of the composites. Additions of fly ash reduced bubble or void formation in the composites, while toughening the composites and improving adhesion between the fiber and matrix. Samples with 4 w% of fiber and 2 wt% of fly ash composites showed high tensile strength and hardness properties, while 2 wt% of fiber composites showed high flexural strength.